2021
DOI: 10.1177/0193945921992540
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Changes in Health Perception in Patients with Heart Failure

Abstract: Determination of modifiable factors associated with changes in health perception can be beneficial for improvement in health perception and health-related quality of life. The purpose of this study was to examine if changes in physical symptoms, functional status, and depressive symptoms were associated with changes in health perception at three months and the mediator effect of physical symptoms. Data were collected at baseline and three months later (N = 65). Process Macro for SPSS was used to analyze the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Heo et al. (2021) also highlighted that the functional status had no mediation effect on the relationship between symptoms and overall health perception (Heo et al., 2021). In contrast to these findings, Beverly et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heo et al. (2021) also highlighted that the functional status had no mediation effect on the relationship between symptoms and overall health perception (Heo et al., 2021). In contrast to these findings, Beverly et al.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that other variables may be involved in this process. Heo et al ( 2021) also highlighted that the functional status had no mediation effect on the relationship between symptoms and overall health perception (Heo et al, 2021). In contrast to these findings, Beverly et al (2013) found that physical and social function status mediated the effects of shortness of breath and fatigue symptoms on overall health perception in HF patients, and physical symptoms had no significant direct effects on overall health perception in their model (Beverly et al, 2013).…”
Section: Modification Indices Valuementioning
confidence: 98%
See 2 more Smart Citations
“…The depressive symptoms could have contributed to worsening QoL in our patients by impacting on their physical symptoms, such as difficulty walking, difficulty climbing stairs, and fatigue. In fact, Heo et al (2021) have previously shown that physical symptoms are mediators of the relationship between depressive symptoms and patients’ self-perceived health status.…”
Section: Discussionmentioning
confidence: 99%